Structural levels of the nucleation and growth of fatigue crack in 17Mn1Si steel pipeline after long-term service - Maruschak, Pavlo; Panin, Sergey; Vlasov, Ilya; Prentkovskis, Olegas; Danyliuk, Iryna (Transport, 2015)
The majority of modern gas pipelines in Ukraine, Lithuania and Russia have been operating for more than 30–40 years. The problem of forecasting residual life-time of materials comprising such gas pipelines calls for study of their degradation kinetics as well as requires to determine its relationship with the strain-force loading parameters. The aim of the paper is to study the kinetics of fracture in order to range mechanisms of cyclic deformation of 17Mn1Si steel at nucleation and growth of a fatigue crack. Flat specimens were cut out from a fragment of 17Mn1Si steel pipe after 40 years of service. Microstructures of specimens were examined. In the paper, an attempt was made to apply the combined approach to study of deformation and fracture based on the following research parameters from nonlinear fracture mechanics: physical mesomechanics and numerical fractography. First published online: 28 Jan 2015